The association between physical dependency and the presence of neuropsychiatric symptoms, with the admission of people with dementia to a long-term care institution: A prospective observational cohort study☆. Issue 5 (May 2015) - Risco, Ester; Cabrera, Esther; Jolley, David; Stephan, Astrid; Karlsson, Staffan; Verbeek, Hilde; Saks, Kai; Hupli, Maija; Sourdet, Sandrine; Zabalegui, Adelaida; RightTimePlaceCare Consortium, 1
Abstract Background Dementia is a progressive neurological disorder that causes a high degree of dependency. This dependency has been defined as an increased need for assistance due to deterioration in cognition and physical functioning, and changes in behavior. Highly dependent people with dementia are more likely to be institutionalized. Objectives To investigate the association between specific categories of physical dependency and the presence of neuropsychiatric symptoms in people with dementia admitted to a long-term care institution. Design A prospective observational cohort study. Settings Home care and long-term care institutions in eight European countries. Participants People with dementia living at home but at risk of institutionalization and recently institutionalized people with dementia. Method Baseline and 3-month follow-up interviews were performed between November, 2010 and April, 2012. The sample consisted of 116 recently institutionalized dementia sufferers and 949 people with dementia still living at home. Physical dependency was measured using the Katz Activity of Daily Living index, and neuropsychiatric symptoms were assessed through The Neuropsychiatric Inventory. Specific categories of dependency were analyzed by performing a logistic regression analysis. This followed examination of baseline characteristics to define the degree of physical dependency, as factors associated with institutionalization, and evaluation of the same characteristics at 3-month follow-up to detect changes in the degree of physical dependency and neuropsychiatric symptoms associated with recent admission to a long-term care institution. Results Toileting, dressing and continence dependency was higher in institutionalized people than in those receiving home-care. Delusion, hallucination, agitation, anxiety, apathy, motor-disturbances, night-time behavior and eating disorders were also worse in the institutionalized. Logistic regression analysis showed that independent factors significantly associated with being recently institutionalized were toileting (odds ratio = 2.3; 95% confidence interval = 1.43–3.71) and motor disturbances (odds ratio = 1.81; 95% confidence interval = 1.15–2.87). Conclusions This study supports the association between type and degree of physical dependency in people with dementia and long-term institutionalization. Institutionalization is associated with physical dependency and the presence of neuropsychiatric symptoms.